Confiabilidade de pilares curtos em concreto de alta resistência dimensionados segundo a ABNT NBR 6118 / 2014 - Raphael Nonato Cabana Vieira (2017)
Several studies have demonstrated the economic viability of high strength concrete (HSC) in the columns of the lower floors of high-rise buildings, bridges and special structures. ABNT NBR 6118:2007 had its use limited to concretes with characteristic strength up to 50 MPa. In line with international standards, NBR 6118:2014 has incorporated into its scope concretes with characteristic strengths in the range 50 to 90 MPa. These changes in the new version of the Brazilian standard for design of concrete structures are aimed to satisfy designers needs and the current availability of HSC in Brazil. Given their increased use, type of failure and importance to the structural integrity, the safety assessment of HSC columns is a very important subject. In the case of reinforced concrete columns, several parameters involved in the structural design process are uncertain (concrete compressive strength, cross section dimensions, loads, etc.). Thus, the structural safety can be established only in probabilistic terms. In order to simplify the design process, target reliability levels are satisfied by prescribing partial factors (material and load factors) in the limit state design procedures. In this study, the reliability indexes implicit in the design of ecentrically-loaded short HSC columns according ABNT NBR 6118: 2014 were evaluated. 400 columns were chosen, which were analyzed using the two stress-strain models proposed by this design code. The influence of several parameters (concrete compressive strength, ratio between dead and live loads, load eccentricity, longitudinal steel ratio and cross-sectional height) was investigated. It was observed that the variables compressive strength of the concrete and the load ratio have the largest influence on the probabilities of failure (and reliability indexes) of reinforced concrete columns designed according to ABNT NBR 6118 / 2014.